MULTIFUNCTIONAL MUTANTS OF Azospirillum sp. WITH ENHANCED CAPABILITY OF SOLUBILIZING PHOSPHORUS, FIXING NITROGEN AND PRODUCING INDOLE ACETIC ACID - Riyanti, Eny Ida; Hadiarto, Toto; Susilowati, D.N. (Indonesian Journal of Agricultural Science, 2012)
Azospirillum sp. have long been known as biofertilizer for plant growth because of its capability to produce phytohormones and fix nitrogen from the atmosphere. Multifunctional Azospirillum strain Aj Bandung 6.4.1.2 isolated in 2009 from cauliflower (Brassica oleracea) rhizosphere in Lembang, Bandung, West Java, was capable of fixing nitrogen, solubilizing tricalcium-phosphate, and producing phytohormone indole acetic acid (IAA). The study aimed to modify the multifunctions of Azos-pirillum sp. for better capability of fixing N2, solubilizing P, and producing IAA using ethyl methanesulfonate and 1-methyl-3-nitro-1-nitrosoguanidine (EMS) mutagen. The study was conducted at Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development (ICABIOGRAD) in 2010. The results showed that this strain was genetically mutagenized using EMS for better performance in solubilizing P, fixing N2 (nitrogenase activity), and producing phytohormone (IAA). The optimum concentration and the length of incubation time for the process have been determined. Nine selected mutants with increasing capability to solubilize P (determined by clear-zone formation on Pikovskayaâs medium) have been characterized for nitrogenase activities and IAA production compared to wild type Aj Bandung 6.4.1.2. The effect of mutagenesis on IAA produc-tion and nitrogenase activities varied among the mutans. Two mutants, AzM 3.7.1.16 and AzM 1.7.2.12, showed superiority in the production of IAA, while two mutants, AzM 1.5.1.14 and AzM 3.7.1.15, were superior in nitrogenase activities. The EMS mutagenesis of Azospirillum sp. showed enhanced dissolving capa-bility of unsoluble phosphate (tricalciumphosphate) and increased IAA production and nitrogenase activity. Â